2021
DOI: 10.1038/s41598-021-97503-0
|View full text |Cite
|
Sign up to set email alerts
|

Underlying hemodynamic differences are associated with responses to tilt testing

Abstract: Aim of this study was to explore whether differences in resting hemodynamic parameters may be associated with tilt test results in unexplained syncope. We analyzed age, gender, systolic (SBP), diastolic blood pressure (DBP) and heart rate (HR) by merging three large databases of patients considered likely to be of vasovagal reflex etiology, comparing patients who had tilt-induced reflex response with those who did not. Tilt-induced reflex response was defined as spontaneous symptom reproduction with characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The above pathophysiological findings suggest the reduced capacity to compensate for lower systolic BP, expressed by lower diastolic BP and HR. Consistently, lower resting systolic BP (≤128 mm Hg) and absence of hypertension have been identified as independent predictors of TT positivity, confirming that reflex syncope susceptibility is strongly related to hemodynamic reserve, which is reduced in presence of lower BP [19]. Therefore, three different hemodynamic profiles can be outlined, including (1) individuals with stable cardiovascular homeostasis; (2) individuals with a predisposition to syncope and well-functioning compensatory mechanisms, allowing for increased tolerance to orthostatic stress and TT; (3) individuals with a more pronounced predisposition to syncope due to the suboptimal compensatory capacity, making them more prone to develop reflex syncope during TT.…”
Section: Recent Advances In the Pathophysiology Of Syncope W H A T ' S N E W ?supporting
confidence: 55%
See 1 more Smart Citation
“…The above pathophysiological findings suggest the reduced capacity to compensate for lower systolic BP, expressed by lower diastolic BP and HR. Consistently, lower resting systolic BP (≤128 mm Hg) and absence of hypertension have been identified as independent predictors of TT positivity, confirming that reflex syncope susceptibility is strongly related to hemodynamic reserve, which is reduced in presence of lower BP [19]. Therefore, three different hemodynamic profiles can be outlined, including (1) individuals with stable cardiovascular homeostasis; (2) individuals with a predisposition to syncope and well-functioning compensatory mechanisms, allowing for increased tolerance to orthostatic stress and TT; (3) individuals with a more pronounced predisposition to syncope due to the suboptimal compensatory capacity, making them more prone to develop reflex syncope during TT.…”
Section: Recent Advances In the Pathophysiology Of Syncope W H A T ' S N E W ?supporting
confidence: 55%
“…Individual hemodynamic features not only determine the predisposition to reflex syncope but also affect TT response. Another recent study has demonstrated that tilt-positive patients have lower systolic BP, diastolic BP, and HR compared with tilt-negative patients with similar presentations, independently of age and sex [19]. The above pathophysiological findings suggest the reduced capacity to compensate for lower systolic BP, expressed by lower diastolic BP and HR.…”
Section: Recent Advances In the Pathophysiology Of Syncope W H A T ' S N E W ?mentioning
confidence: 88%
“…We did not collect data on subtypes of syncope, recurrent syncope, or seizures. While most cases of syncope in the general population are thought to be reflex syncope or orthostatic hypotension, [14] , [1] , [2] , [3] , [4] , [5] our data may partly reflect seizures and cardiac abnormalities. Syncope due to cardiac or other conditions with high mortality is evidently underrepresented.…”
Section: Discussionmentioning
confidence: 81%
“…Hypotensive susceptibility is thought to be central to the pathophysiology of syncope. [1] , [2] , [4] , [5] With risk factors including low blood pressure, low BMI, decreased skeletal muscle tone and reduced circulating volume, a hypotensive tendency is thought to contribute to the acute drop in CO that leads to syncope, [1] , [2] , [4] , [5] , [14] but the pathophysiology of “hypotensive susceptibility” remains unclear. [1] , [4] , [5] , [14] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation